Extended range proteomic analysis of blood plasma from schizophrenia patients - Petrovskiy, Denis V.; Butkova, Tatiana V.; Nikolsky, Kirill S.; Kopylov, Arthur T.; Nakhod, Valeriya I.; Kulikova, Liudmila I.; Malsagova, Kristina A.; Kibrik, Nikolai D.; Rudnev, Vladimir R.; Izotov, Alexander A.; Kaysheva, Anna L. (Frontiers in Molecular Biosciences, 2024)
IntroductionThe high prevalence of schizophrenia worldwide makes it necessary to proceed from subjective assessment of patient’s clinical symptoms in diagnosis making to searching for circulating blood biomarkers. On the one hand, searching for molecular markers and targets for therapeutics will make it possible to refine and detail the molecular mechanisms of pathology development, while on the other hand, it will offer new opportunities for elaborating novel approaches to disease diagnosis and enhance efficacy and timeliness of drug therapy.MethodsIn this study, we performed an extended-range proteomic analysis of plasma samples collected from 48 study subjects with confirmed diagnosis of schizophrenia and 50 healthy volunteers. The high-resolution tandem mass spectra recorded in the data-dependent acquisition mode were analyzed using the MaxQuant algorithm for the library of known protein sequences and the PowerNovo algorithm for de novo protein sequencing.ResultsIt was demonstrated that both strategies show similar results for high-abundance proteins (≥1 μg/mL). For mid-abundance (10 ng/mL – 1 μg/mL) and low-abundance (<10 ng/mL) proteins, the results obtained by the two search strategies complement each other.DiscussionGroup-specific proteins for the samples of schizophrenia patients were identified, presumably being involved in synaptic plasticity, angiogenesis, transcriptional regulation, protein stabilization and degradation.